2020
DOI: 10.1053/j.gastro.2020.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Lipotoxicity and Cytokine Storm in Severe Acute Pancreatitis and COVID-19

Abstract: See "Mortality from coronavirus disease 2019 increases with unsaturated fat and may be reduced by early calcium and albumin supplementation," by El-Kurdi B, Khatua B, Rood C, et al, on page 1015.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
62
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(66 citation statements)
references
References 15 publications
1
62
0
3
Order By: Relevance
“…Thus, this pathway of virus induced lipotoxicity and cytokine storm [ 28 ] can explain the pancreatic injury. In fact, the cytokine profile of both AP and COVID-19 infection has been found to be similar, with increased levels of IL-6, IL-8 and IL-10 [ 29 ].…”
Section: Pathophysiology Of Pancreatic Injurymentioning
confidence: 99%
“…Thus, this pathway of virus induced lipotoxicity and cytokine storm [ 28 ] can explain the pancreatic injury. In fact, the cytokine profile of both AP and COVID-19 infection has been found to be similar, with increased levels of IL-6, IL-8 and IL-10 [ 29 ].…”
Section: Pathophysiology Of Pancreatic Injurymentioning
confidence: 99%
“…More recently, research has shown a significant similarity in cytokine elevations between patients with severe AP and those with severe COVID-19. 13 This suggests that therapeutic removal of cytokines through early supplementation with calcium and albumin may improve outcomes in patients with both diseases. 13 The concentration of glucose increases during refeeding, leading to hyperglycemia.…”
Section: Introductionmentioning
confidence: 99%
“…13 This suggests that therapeutic removal of cytokines through early supplementation with calcium and albumin may improve outcomes in patients with both diseases. 13 The concentration of glucose increases during refeeding, leading to hyperglycemia. As a consequence, insulin secretion increases, stimulating the anabolic pathway and leading to intracellular uptake of phosphate, which is significant for cellular metabolism of macronutrients for energy production.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypocalcemia [ 3 ], hypoalbuminemia [ 4 ], and the cytokine storm [ 5 ] including IL-6 elevation [ 4 , 6 ] can be induced by the unbound [ 4 ] unsaturated fatty acids [ 7 ] released during severe COVID-19 infection. This occurs due to adipose lipolysis (in agreement with obesity worsening COVID-19 [ 8 ]), and causes distributive shock, renal failure and arrhythmias via endothelial, epithelial and cardiomyocyte injury respectively [ 4 ].…”
mentioning
confidence: 99%